REGENERASI SARAF PERIFER - Ashalia Chandra Dewi, Shahdevi Nandar Kurniawan, Machlusil Husna, Masruroh Rahayu (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION PERIPHERAL NERVES CONSIST OF ALL NERVOUS SYSTEM OUTSIDE THE BRAIN AND SPINAL CORD IF THERE IS A PERIPHERAL NERVE INJURY THERE WILL BE A SERIES OF COMPLEX PROCESS TO DISPOSE TISSUE DAMAGE AND START RECOVERY THE RATE OF REGENERATION DEPENDS ON THE SEVERITY OF THE INJURY THE ONSET OF INNERVATION AND PERIPHERAL NERVE CONDITION ITSELF HOWEVER PERIPHERAL NERVE DEGENERATION AND REGENERATION PROCESS IS NOT FULLY UNDERSTOOD